2012
DOI: 10.3346/jkms.2012.27.9.993
|View full text |Cite
|
Sign up to set email alerts
|

The Time between Paraquat Ingestion and a Negative Dithionite Urine Test in an Independent Risk Factor for Death and Organ Failure in Acute Paraquat Intoxication

Abstract: To identify a prognostic marker that is less sensitive to variations in the elapsed time since paraquat ingestion, we assessed the time between paraquat ingestion and a negative dithionite urine test as a prognostic parameter in patients with acute paraquat intoxication. Forty-one patients with acute paraquat intoxication were enrolled in this study and analyzed to verify significant determinants of mortality and organ dysfunction. The amount of paraquat ingested, paraquat plasma levels, and the time to a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 24 publications
(28 reference statements)
3
37
1
Order By: Relevance
“…Similarly, continuous venovenous haemodiafiltration was successfully used in the rescue of a patient with a high dose PQ exposure of 36.48 mg/kg 21 . Thus, more patients might be saved if PQ elimination or renal replacement therapy can be more efficiently administered a short time after poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, continuous venovenous haemodiafiltration was successfully used in the rescue of a patient with a high dose PQ exposure of 36.48 mg/kg 21 . Thus, more patients might be saved if PQ elimination or renal replacement therapy can be more efficiently administered a short time after poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no prognostic models have been prospectively validated because of issues in their development such as small sample size, differences in the degree of severity, and complicated exclusion criteria 24 . The urine dithionite test is a simple index for clinical diagnosis and prediction of prognosis of PQ poisoning; however, false results limit its usefulness 25 . Our study is one of the few performed to date addressing serum UA levels and laboratory parameters in a clinical context with relatively large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Early prognosis of PQ poisoning is significant for both patients and doctors [3]. Studies have shown that the mortality rate of PQ poisoning is highly correlated with ingested PQ amount or PQ concentrations in plasma and urine (within 4-24 hr elapsed from ingestion) [4,5]. Hsu et al [6] found that early haemoperfusion (HP) after PQ exposure may reduce the mortality specifically and that HP <4.0 or <5.0 hr can reduce the relative risk of mortality by approximately 81% or 51%, respectively.…”
Section: Paraquat (11mentioning
confidence: 99%